Movement of Indian Antarctic station Maitri into auroral oval during geomagnetic disturbance - Banola, S.; Dhar, Ajay; Rajaram, G. (1997)
During the 13th Summer Indian Antarctic Expedition (Dec 1993 - March 1994), fluxgate magnetometers were operated at the Indian Antarctic locations MAITRI (MAI) and DAKSHIN GANGOTRI (DG). The variations of the X, Y, Z geomagnetic components when compared between magnetically Quiet days, moderately Disturbed days, and clearly Disturbed days, indicate that during quiet times, the Indian stations occupy a sub-auroral position; with increasing disturbance, they come into the auroral oval, and then the geomagnetic variations bear the signature of the auroral electrojet (AE) and field-aligned currents (FAC). Ionospheric horizontal current densities in the north-south and east-west directions are estimated from the variations in the geomagnetic components using the Biot-Savart law. They indicate that the current densities over MAI and DG increase with increasing electromagnetic disturbance in geospace, more sharply in the Dawn sector than in the Dusk sector.